Knowledge-intensive business services – state and forecast of development - Skórska, Anna (Wiedzochłonne usługi biznesowe – stan i perspektywy rozwoju, 2015)
Knowledge-intensive business services are one of the most dynamically developing areas in contemporary economies and at the same time they constitute one of the fundamental pillars of a knowledge economy. The services are provided by private enterprises, the activity of which is mostly based on the professional knowledge of workers. They supply knowledge-based products and services delivering satisfaction to intermediate demand. These are related, among others, to research and development activity, legal activity, activity in the sphere of architecture and engineering or information technology services. Interest in knowledge-intensive business services (KIBS) is a result of rapidly occurring changes in recent decades, the creation of a knowledge economy and an information society, the growing importance of knowledge and human capital as well as innovativeness. The goal of the article is to present the changes occurring in the sphere of KIBS in Poland between 2005 and 2012 with special attention focussed on employment and its forecast
Ekonometria = Econometrics, 2015, Nr 3 (49), s. 66-77
Keywords: services; employment; development; KIBS; usługi; zatrudnienie; rozwój; wiedzochłonne usługi biznesowe